Integration and contribution of artificial intelligence in writing scientific papers - Ekowati, Maria Atik Sunarti; Dananti, Kristyana; Wening, Sri; Darsini, Darsini (Institute of Computer Science (IOCS), 2024)
This research aims to explore the integration and contribution of artificial intelligence (AI) in the process of writing scientific papers, examining various AI applications, such as writing tools based on natural language processing (NLP), automatic assessment systems for writing quality, and reference management platforms automatic. With the rapid advancement of technology, AI has shown great potential in improving the efficiency and quality of academic writing. This study analyzes how AI can help in various stages of writing, from literature searches, structuring papers, to proofreading and improving writing style. The research also highlights key differences between traditional approaches to writing scientific papers and AI-powered approaches. Previously, scientific writing relied entirely on the individual writer's ability to conduct research, organize information, and write effectively. These conventional methods are often time consuming and prone to human error. In contrast, AI integration allows the automation of some time-consuming tasks, such as data processing and text editing, so that authors can focus on the creative and analytical aspects of their research. The results of this research show that the use of AI in scientific writing not only increases efficiency but can also improve the quality and accuracy of scientific papers. AI is able to provide relevant suggestions based on existing data, identify grammatical and writing errors, and assist in finding the right references. Thus, AI integration can become an invaluable tool for researchers and academics in producing high-quality scientific work.